Prebiotic prevents impaired kidney and renal Oat3 functions in obese rats - Keerati Wanchai (2018)
© 2018 Society for Endocrinology Published by Bioscientifica Ltd. Obesity is health issue worldwide, which can lead to kidney dysfunction. Prebiotics are non-digestible foods that have beneficial effects on health. This study aimed to investigate the effects of xylooligosaccharide (XOS) on renal function, renal organic anion transporter 3 (Oat3) and the mechanisms involved. High-fat diet was provided for 12 weeks in male Wistar rats. After that, the rats were divided into normal diet (ND); normal diet treated with XOS (NDX); high-fat diet (HF) and high-fat diet treated with XOS (HFX). XOS was given daily at a dose of 1000 mg for 12 weeks. At week 24, HF rats showed a significant increase in obesity and insulin resistance associated with podocyte injury, increased microalbuminuria, decreased creatinine clearance and impaired Oat3 function. These alterations were improved by XOS supplementation. Renal MDA level and the expression of AT1R, NOX4, p67 phox , 4-HNE, phosphorylated PKCα and ERK1/2 were significantly decreased after XOS treatment. In addition, Nrf2-Keap1 pathway, SOD2 and GCLC expression as well as renal apoptosis were also significantly reduced by XOS. These data suggest that XOS could indirectly restore renal function and Oat3 function via the reduction of oxidative stress and apoptosis through the modulating of AT1R-PKCα-NOXs activation in obese insulin-resistant rats. These attenuations were instigated by the improvement of obesity, hyperlipidemia and insulin resistance.